First molecular identification of Entamoeba moshkovskii in Malaysia - ANUAR, TENGKU SHAHRUL; AL-MEKHLAFI, HESHAM M.; GHANI, MOHAMED KAMEL ABDUL; AZREEN, SITI NOR; SALLEH, FATMAH MD; GHAZALI, NURAFFINI; BERNADUS, MEKADINA; MOKTAR, NORHAYATI (Parasitology, 2012)
Entamoeba moshkovskii and Entamoeba dispar are microscopically indistinguishable from the pathogenic species Entamoeba histolytica. Although sporadic cases of human infection with E. moshkovskii have been reported, the amoeba is still considered primarily as a free-living amoeba. A cross-sectional study was carried out among Orang Asli communities in 3 different states of Peninsular Malaysia. Fecal samples were examined by formalin-ether sedimentation and trichrome staining techniques and then single-round PCR assay was used to detect E. moshkovskii. Out of 500 fecal samples examined microscopically, 93 (18·6%) samples were positive for E. histolytica/E. dispar/E. moshkovskii complex cysts and/or trophozoites. PCR products were detected in 106 fecal samples. E. moshkovskii isolates were detected in 13 (12·3%) fecal samples. Of the 13 E. moshkovskii-positive samples, 5 were of single isolation of E. moshkovskii, 6 were also positive for E. dispar, and only 2 samples were positive for E. dispar and E. histolytica. Moreover, 3 E. moshkovskii-positive samples were collected from symptomatic individuals while the remaining 10 samples were from asymptomatic subjects. This is the first report on the identification of E. moshkovskii in Malaysia. Further studies are needed to confirm the pathogenicity of E. moshkovskii infection and determine the epidemiology among Orang Asli communities in Malaysia.